Occurrence of Charcoal Rot in Globe Artichoke and Assessment of Inoculation Techniques for Pathogenicity and Management - Aydoğdu,Mehmet (2022)
Abstract Macrophomina phaseolina is a polyphagous fungus causing substantial yield losses in many plant species. In 2017, M. phaseolina was found to be causal agent of wilting and stunting symptoms of globe artichoke (Cynara scolymus) in the Mediterranean region of Turkey. There is no knowledge about M. phaseolina in globe artichoke and applicable management practice in cultivation of the crop. In the present study, the causal agent was characterized in vitro and in vivo studies. Pathogenicity tests were carried out using seedlings of globe artichoke and nine plant species (sunflower, chickpea, soybean, sesame, peanut, wheat, maize, cotton and sorghum) in a greenhouse. In addition, five inoculation techniques were assessed to determine the most suitable method for screening resistance to M. phaseolina in globe artichoke. Significant (P˂0.01) variations were found among the inoculation techniques. Depending on each inoculation technique, death of lateral roots and distinct lesions up to 5.38 cm occurred on primary roots and crowns of globe artichoke. M. phaseolina also caused lesions ranging from 1.43 to 9.63 cm on primary roots including crown and stems of tested plant species. M. phaseolina was pathogenic to globe artichoke and all the tested plant species, confirming its polyphagous nature. This is the first record of M. phaseolina causing root and crown rot in globe artichoke in the world. Moreover, the present study suggested that toothpick inoculation technique could be used for screening resistance to M. phaseolina in globe artichoke.